Retrospective Analysis of Onychomycosis Risk Factors Using the 2003-2014 National Inpatient Sample - Vrusha Shah; Amar Desai; Shari Lipner (Mattioli1885, 2024)
Introduction: Onychomycosis, a fungal nail infection, is associated with significant morbidity and negative impact on quality of life. Therefore, understanding associated risk factors may inform onychomycosis screening guidelines. Objectives: This retrospective study investigated common demographic and comorbidity risk factors among hospitalized patients using the National Inpatient Sample. Methods: The 2003-2014 National Inpatient Sample (NIS) database was used to identify onychomycosis cases and age and sex matched controls in a 1:2 ratio. Chi-square tests and T-tests for independent samples were utilized to compare categorical and continuous patient factors. Demographic and comorbidity variables significant (p<0.05) on univariate analysis were analyzed via a multivariate regression model with Bonferroni correction (p<0.0029). Results: 119,662 onychomycosis cases and 239,324 controls were identified. Compared to controls, onychomycosis patients frequently were White (69.0% vs. 68.0%; p<0.001), Black (17.9% vs. 5.8%; p<0.0001), and insured by Medicare or Medicaid (80.1% vs. 71.1%; p<0.0001). Patients had greater hospital stays (9.69 vs. 5.39 days; p<0.0001) and costs ($39,925 vs. $36,720; p<0.001) compared to controls. On multivariate analysis, onychomycosis was commonly associated with tinea pedis (OR: 111.993; p<0.0001), human immunodeficiency virus (OR: 4.372; p<0.001), venous insufficiency (OR: 6.916; p<0.0001), and psoriasis (OR: 3.668; p<0.001). Conclusion: Onychomycosis patients had longer hospital stays and greater costs compared to controls. Black patients were disproportionately represented among cases compared to controls. Onychomycosis was associated with tinea pedis, venous insufficiency, human immunodeficiency virus, psoriasis, obesity (BMI ≥ 30 kg/m2), peripheral vascular disease, and diabetes with chronic complications, suggesting that inpatients with onychomycosis should be screened for these conditions.